2013
DOI: 10.3233/wor-121484
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, quality of life and emotional profile in general practitioners and psychiatrists

Abstract: OBJECTIVE: Many studies confirm that psychological factors and burnout in physicians are interconnected. It is however not known, whether quality of life is another factor that plays a role in this connection.The aim of this study was to explore the correlation between quality of life and emotional profile with the level of burnout in physicians. PARTICIPANTS: 120 physicians participated in this study, i.e. sixty general practitioners (GPs) and sixty psychiatrists. METHODS:The General Health Questionnaire (GHQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Of the included studies, 28 were quantitative, [24][25][26][27][28][29][30][33][34][35][36][37][38][39][40][44][45][46][47][48][49][50][51][52][53][54][55][56] two were qualitative, 31,32 one was interventional 41 and two had mixed methodology. 42,43 Countries of origin Studies originated from Australia, 29,40,48,55 New Zealand, 28,31,38,39 the UK, 30,34,43,47 the USA, 24,26,52 Canada, 35,50 Italy, 25,…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the included studies, 28 were quantitative, [24][25][26][27][28][29][30][33][34][35][36][37][38][39][40][44][45][46][47][48][49][50][51][52][53][54][55][56] two were qualitative, 31,32 one was interventional 41 and two had mixed methodology. 42,43 Countries of origin Studies originated from Australia, 29,40,48,55 New Zealand, 28,31,38,39 the UK, 30,34,43,47 the USA, 24,26,52 Canada, 35,50 Italy, 25,…”
Section: Methodsmentioning
confidence: 99%
“…27 Several studies involved a combination of countries 40,45,46,49 and six studies did not specify location. 32,37,41,51,53,56 Populations Twenty studies involved psychiatry doctors only, comprising psychiatrists, 25,27,31,32,[37][38][39][40][41][43][44][45]47,48,52 psychiatry trainees 35,42,55 or a combination of both. 24,49 Only three studies provided an indication of subspecialty, including child and adolescent, 36,40 adult 36 and forensic psychiatry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors affecting the phenomenon of physician burnout have been considered in literature, with reported risk factors being younger age, longer working hours with high workload, low job satisfaction, negative or poor personal relationships and interpersonal demands, job insecurity, and female gender, as well as a weak association with specialty [13][14][15]. These findings place physicians in common with other healthcare professions [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed that physicians and nurses experience very high levels of burnout, dissatisfaction, and work-related stress [24]. Burnout contributes to poor health outcomes of health care professionals, both in terms of physical illness and emotional problems [5].…”
Section: Introductionmentioning
confidence: 99%